Artificial Intelligence in the Thought of Imam al-Ash‘ari - Rahman, Andhika; Abd. Rahman Hamid; Muhammad Akmansyah; Muslimin (IAIN Parepare, 2025)
In everyday language, AI is not considered mute because it can produce speech; however, from the perspective of kalam, the presence of kalam nafsi is required to negate muteness. The research problem, which centers on the distinction in the meaning of muteness, gives rise to three main issues to be analyzed: (1) the possibility of qualia in AI, (2) AI’s potential to speak, and (3) the source of the grammatical utterances generated by AI. This study is descriptive and qualitative in nature, employing a literature review method. The results of this study reveal three key findings: first, AI does not possess qualia; second, AI is essentially a mute subject that only produces speech mechanically; and third, the source of AI’s utterances is its designer. Theoretically, this research expands the concept of kalam in Imam al-Ash‘ari’s thought, which was previously focused solely on God, toward the domain of created beings in this case, AI. Practically, this study shifts our linguistic perspective by highlighting that the AI we converse with is a mute subject, whereas a mute human being actually possesses inner speech. Keywords: . AI, Imam al-Ash‘ari, Muteness, Kalam, Qualia